2021
DOI: 10.3390/nu13082613
|View full text |Cite
|
Sign up to set email alerts
|

Brown Seaweed Food Supplementation: Effects on Allergy and Inflammation and Its Consequences

Abstract: Multiple health benefits have been ascribed to brown seaweeds that are used traditionally as dietary component mostly in Asia. This systematic review summarizes information on the impact of brown seaweeds or components on inflammation, and inflammation-related pathologies, such as allergies, diabetes mellitus and obesity. We focus on oral supplementation thus intending the use of brown seaweeds as food additives. Despite the great diversity of experimental systems in which distinct species and compounds were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 171 publications
(293 reference statements)
1
19
0
1
Order By: Relevance
“…O. japonicas crude polysaccharide showed antagonistic effect in alloxan-induced diabetic mice while its purified form of polysaccharide showed anti-diabetic activity in streptozotocin-induced diabetic rats [64]. Several lines of evidences delineated the experimental affirmation of seaweed polysaccharides in the treatment of different diseases such as obesity, diabetes, allergies, inflammation and hepatic steatosis [65][66][67][68][69][70]. In concordance with the beneficial effects of polysaccharides our research group isolated the polysaccharide from seaweed, Dictyopteris divaricata.…”
Section: Discussionmentioning
confidence: 63%
“…O. japonicas crude polysaccharide showed antagonistic effect in alloxan-induced diabetic mice while its purified form of polysaccharide showed anti-diabetic activity in streptozotocin-induced diabetic rats [64]. Several lines of evidences delineated the experimental affirmation of seaweed polysaccharides in the treatment of different diseases such as obesity, diabetes, allergies, inflammation and hepatic steatosis [65][66][67][68][69][70]. In concordance with the beneficial effects of polysaccharides our research group isolated the polysaccharide from seaweed, Dictyopteris divaricata.…”
Section: Discussionmentioning
confidence: 63%
“…In the United States of America, due to the potential of crustacean contamination of seaweed cultivated on longlines, crustacean shellfish allergens (especially due to the protein tropomyosin) have been described as significant chemical hazards in seaweed (Concepcion et al, 2020). In contrast, other studies ascribe anti-allergic properties to some seaweeds (especially brown seaweed) (Farrohki et al, 2009;Samee et al, 2009;Olsthoorn et al, 2021). Miyake et al (2006) suggested a link between higher seaweed intake and lower prevalence of allergic rhinitis among Japanese young female adults.…”
Section: Allergensmentioning
confidence: 93%
“…Ekstrak Sargassum pada model mencit menunjukkan aktivitas antialergi dengan mensupresi degranulasi mast cell dan basofil. Administrasi oral polisakarida dari Sargassum (200mg/kg selama 6 hari) diidentifikasi meningkatkan imunitas pada model tikus terimunosupresi (Olsthoorn et al, 2021).…”
Section: Saraswati Et Al (2019)unclassified